Ultra high speed SHA-256 hashing cryptographic module for IPSEC hardware/software codesign - Michail, Harris; Athanasiou, George S.; Kritikakou, Angeliki S.; Goutis, Costas E.; Gregoriades, Andreas; Papadopoulou, Vicky (My University, 2010)
Nowadays, more than ever, security is considered to be critical issue for all electronic transactions. This is the reason why security services like those described in IPSec are mandatory to IPV6 which will be adopted as the new IP standard the next years. Moreover the need for security services in every data packet that is transmitted via IPv6, illustrates the need for designing security products able to achieve higher throughput rates for the incorporated security schemes. In this paper such a design is presented which manages to increase throughput of SHA-256 hash function enabling efficient software/hardware co-design.
Keywords: Hardware design; Hash-Functions; High-Throughput; IPSec; SHA-256; VLSI